2017
DOI: 10.1128/genomea.00358-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Plant Growth-Promoting Endophytic Streptomyces sp. GKU 895 Isolated from the Roots of Sugarcane

Abstract: Streptomyces sp. GKU 895 is an endophytic actinomycete isolated from the roots of sugarcane. GKU 895 has a genome of 8.3 Mbp and the genome exhibits adaptations related to plant growth-promoting activity. It also has extensive specialized metabolite biosynthetic gene clusters apparent in its genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…We observed a few taxa that were consistently enriched in the sugarcane roots, including Saccharibacteria , Ensifer , Streptomyces , Rhizobium , Devosia , Lentzea , Pseudomonas , Acinetobacter , Ohtaekwangia , Arthrobacter , and Streptophyta . In a previous study, Streptomyces , Rhizobium , and Acinetobacter were shown to be enriched in the sugarcane endophyte community ( Velázquez et al, 2008 ; Rouws et al, 2014 ; Kruasuwan et al, 2017 ). Recent studies on Streptomyces have produced a draft genome sequence, and have shown it to be a plant growth-promoting endophyte ( Kruasuwan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We observed a few taxa that were consistently enriched in the sugarcane roots, including Saccharibacteria , Ensifer , Streptomyces , Rhizobium , Devosia , Lentzea , Pseudomonas , Acinetobacter , Ohtaekwangia , Arthrobacter , and Streptophyta . In a previous study, Streptomyces , Rhizobium , and Acinetobacter were shown to be enriched in the sugarcane endophyte community ( Velázquez et al, 2008 ; Rouws et al, 2014 ; Kruasuwan et al, 2017 ). Recent studies on Streptomyces have produced a draft genome sequence, and have shown it to be a plant growth-promoting endophyte ( Kruasuwan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study, Streptomyces , Rhizobium , and Acinetobacter were shown to be enriched in the sugarcane endophyte community ( Velázquez et al, 2008 ; Rouws et al, 2014 ; Kruasuwan et al, 2017 ). Recent studies on Streptomyces have produced a draft genome sequence, and have shown it to be a plant growth-promoting endophyte ( Kruasuwan et al, 2017 ). Although in our study, most bacterial taxa of lower rank were not sequenced at sufficiently high coverage to enable powerful comparisons, we did observe enrichment of the genus Pseudomonas , members of which are well-known plant growth-promoting endophytic bacteria.…”
Section: Discussionmentioning
confidence: 89%
“…Supportive evidence comes from several independent studies, reporting S. olivochromogenes from the endosphere of Chinese cabbage roots, potato tubers, medicinal plants and purple henbit (Singh and Gaur 2016 ; Lee et al 2008 ; Doumbou et al 1998 ; Kim et al 2012 ). Additionally, strains similar to S. clavifer were previously isolated from sugarcane, lucerne plants and wheat (Kruasuwan et al 2017 ; Franco et al 2017 ; Misk and Franco 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to indoleacetamide hydrolase pathway nitrilase pathway has also reported in Streptomyces sp. (GKU 895) 37 . Like siderophore, function characterization of IAA pathway by qPCR was earlier reported for almost all strains, showing correlated expression with the IAA production level 13,15,17,19 .…”
Section: Discussionmentioning
confidence: 99%